JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF IMMIGRATION SUPERVISION AT BATAM CENTER PORT IN PREVENTING HUMAN TRAFFICKING CRIMES (A RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE TPI BATAM) - Baginda Raja Harahap; Parameshwara; Bachtiar Simatupang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The criminal act of human trafficking (TPPO) is a highly complex form of transnational crime that continues to increase, especially in border areas such as the city of Batam. As a gateway for people entering and leaving the country, Batam Centre International Port is highly vulnerable to TPPO practices, both in the form of non-procedural migrant worker dispatches and cross-border human exploitation. Therefore, immigration supervision plays a central role in preventing this crime. This study aims to analyse the legal regulations, implementation, obstacles, and efforts undertaken by the Class I Special Immigration Office TPI Batam in carrying out immigration supervision functions to prevent TIP in the Batam Centre Port work area. This research uses normative and empirical juridical methods with a statute and socio-legal approach. Data were obtained through literature study and direct interviews with Immigration officers and related agencies. The theories used as analytical tools consist of the Theory of Legal Effectiveness, Crime Prevention Theory, and the Theory of State Administration Functions. The research results indicate that although various policies have regulated immigration supervision, their implementation has not been optimal due to limited human resources, technology, and a lack of coordination between agencies. These obstacles affect the effectiveness of preventive measures against TIP. Therefore, it is recommended that inter-agency information systems be integrated, regulations updated, regular training for officers provided, and multi-sector collaboration strengthened as measures to reinforce the immigration supervision system at international ports.